Coordination of physiological and structural traits in Amazon forest trees - S. Patiño; N. M. Fyllas; T. R. Baker; R. Paiva; C. A. Quesada; A. J. B. Santos; M. Schwarz; H. ter Steege; O. L. Phillips; J. Lloyd (Biogeosciences, 2012)
Many plant traits covary in a non-random manner reflecting interdependencies associated with "ecological strategy" dimensions. To understand how plants integrate their structural and physiological investments, data on leaf and leaflet size and the ratio of leaf area to sapwood area (ΦLS) obtained for 1020 individual trees (encompassing 661 species) located in 52 tropical forest plots across the Amazon Basin were incorporated into an analysis utilising existing data on species maximum height (Hmax), seed size, leaf mass per unit area (MA), foliar nutrients and δ13C, and branch xylem density (ρx). Utilising a common principal components approach allowing eigenvalues to vary between two soil fertility dependent species groups, five taxonomically controlled trait dimensions were identified. The first involves primarily cations, foliar carbon and MA and is associated with differences in foliar construction costs. The second relates to some components of the classic "leaf economic spectrum", but with increased individual leaf areas and a higher ΦLS newly identified components for tropical tree species. The third relates primarily to increasing Hmax and hence variations in light acquisition strategy involving greater MA, reductions in ΦLS and less negative δ13C. Although these first three dimensions were more important for species from high fertility sites the final two dimensions were more important for low fertility species and were associated with variations linked to reproductive and shade tolerance strategies. Environmental conditions influenced structural traits with ρx of individual species decreasing with increased soil fertility and higher temperatures. This soil fertility response appears to be synchronised with increases in foliar nutrient concentrations and reductions in foliar [C]. Leaf and leaflet area and ΦLS were less responsive to the environment than ρx. Thus, although genetically determined foliar traits such as those associated with leaf construction costs coordinate independently of structural characteristics such as maximum height, others such as the classical "leaf economic spectrum" covary with structural traits such as leaf size and ΦLS. Coordinated structural and physiological adaptions are also associated with light acquisition/shade tolerance strategies with several traits such as MA and [C] being significant components of more than one ecological strategy dimension. This is argued to be a consequence of a range of different potential underlying causes for any observed variation in such "ambiguous" traits. Environmental effects on structural and physiological characteristics are also coordinated but in a different way to the gamut of linkages associated with genotypic differences.